Detecting bacteriuria in a primary maternal and child health care programme. Issue 6626 (26th March 1988) - Joseph, K S; Brahmadathan, K N; Abraham, Sulochana; Joseph, Abraham
Abstract : Urinary tract infection in pregnancy has not been adequately dealt with in developing countries, though its consequences are well recognised. This is primarily because of constraints on resources coupled with a lack of technological infrastructure. An evaluation of the Griess test for the mass screening of urinary tract infection among antenatal women was carried out prospectively using a case-control method. The Griess test was found to be a valid, reliable, and economical screening test for urinary tract infection which can be integrated into a primary maternal and child health care programme.